Development of a magnetic resonance imaging biomarker to improve prognostication in metastatic medulloblastoma - Mitoko, Christine Angeline (2021)
Introduction Metastatic medulloblastoma (MB) manifests in one third of paediatric patients at diagnosis, conferring a poor prognosis. Our limited capacity to detect dissemination at diagnosis and disease recurrence however, results in the erroneous risk stratification of paediatric patients with MB, with serious subsequent prognostic implications.